RECONCEPTUALIZING WOMAN BEAUTY IN DRAMA SERIES MY ID IS GANGNAM BEAUTY - Rane, Zakridatul Agusmaniar (Seshiski: Southeast Journal of Language and Literary Studies, 2022)
Women and beauty are a unity. Beauty as the characteristic of femininity has taken root in a wider social system. It is culturally programmed. The modern beauty myth which is centered on women's bodies is reproduced continuously. The most dominant way of reproduction is through the media. The beauty myth is represented through advertisements, idol appearances, films, and TV series. Beauty myths are felt torturing women, so lately the movement to free women from the shackles of beauty myths is increasingly being voiced. This effort is carried out in various ways for example through writing, criticism, and popular culture. One of them is a drama series My ID is Gangnam Beauty. It is a Korean drama but watched by people around the world, dubbed in many language versions, including English. It carries out a universal issue: the beauty myth. It deconstructs the definition of woman beauty. This paper analyzes what and how beauty is defined in this series. The descriptive qualitative method is used in the analysis process. The result shows that in this series, beauty is still put as women's identity and allure, but beauty is defined as kindness and good behavior. The female main character has an ugly face so she does plastic surgery. People then call her a plastic monster, but she is loved by the most popular boy on her campus. Through this story, the audience is told that true beauty is not good-looking, but it is about attitude and behavior.